Integration of R plasmid Rts1 to the gal region of the Escherichia coli chromosome. - Terawaki, Y (1975)
An R plasmid Rts1 was integrated into the gal region of the chromosome of Escherichia coli XA-7012 (galE) strain by the directed transposition technique. The integration of the Rts1 genome was confirmed mainly by conjugation studies and also by transduction experiments using phage P1. As a result, it was found that the integrated genome contained genes responsible for kanamycin resistance, conjugal transferability, and for autonomous replication. As reported previously, Rts1 is temperature sensitive in replication and inhibits the growth of the host at nonpermissive temperature. However, although a plasmid derived from the integrated Rts1 genome still demonstrates temperature sensitivity upon transfer and high level of kanamycin resistance, this plasmid no longer displays temperature sensitivity in replication and the inhibitory effect on the host. These results indicate that the temperature sensitivity of replication of Rts1 and its inhibitory effect on the host cell are due to the presence of a gene or gene cluster on the Rts1 genome and that the gene(s) is clearly discriminated from the one responsible for the temperature sensitivity of transfer.